Prehrana lesne sove Strix aluco na Kozjanskem (V Slovenija) - Mirt, Branka (Acrocephalus, 2006)
During the period autumn 2002 - spring 2005, 600 pellets of the Tawny Owl Strix aluco from 13 localities were collected, in which 2,028 prey units were found. Mostly, small mammals (50.4%) and insects (38.2%) had been preyed on. A total of 59 taxa were found in the pelleds, of which 21 were mammal and 13 beetle species were identified. The most common prey species were the Yellow-necked Mouse Apodemus flavicollis (17.2%) and the Wood Mouse Apodemus sylvaticus (6.6%). The highest biomass proportion in the Tawny Owl's diet was that for the Pat Dormouse Glis glis (28.3%). The owls fed on prey opportunistically, reflecting a wide feeding niche (H' = 0.886). Seasonal changes in prey species ratio was established. For the very first time, the presence of Alpine Pine Vole Microtus multiplex was noted in the Kozjansko region.
Keywords: lesna sova; prehrana; food; karst; Kras; bird; ptice; sezonska dinamika; Slovenia; Slovenija; Kozjansko